Penguatan Kolaborasi Ekonomi dan Bisnis Perantau Indonesia di Malaysia melalui Pendekatan FGD dalam Kegiatan Majlis Himpunan Erat Dagang Malaysia–Indonesia - Reza Ronaldo; Umi Khulsum; Meilia Risna; Pertiwi Utami; Ferliansyah Zais; Risen Anugrah Ramatullah; Laila Subra; Kiara Basmala Putri; Muhammad Sunni Setiyo (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This international community service program (PKM) aimed to strengthen economic and business collaboration between Indonesian diaspora entrepreneurs in Malaysia and academic institutions in Indonesia. Implemented through a Focus Group Discussion (FGD) approach on August 23–24, 2025, at the Dewan Majlis Perundingan Melayu (MPM), Kuala Lumpur, the program involved 120 participants representing Indonesian universities, the Malaysia International Marketing & Trade Chamber (MIMTC), Persatuan Anak Rantau Indonesia (PARI) Malaysia, and GEO Artha Holding Sdn. Bhd. The program’s success indicators included the signing of 14 Memoranda of Understanding (MoU), the establishment of the ASEANACA Business & Research Council, and measurable improvements in participants’ understanding of business legality, digital literacy, and cross-border collaboration strategies. Post-FGD evaluation showed that 78% of participants gained new business partners, while 65% reported increased knowledge of Malaysian business regulations. Overall, the program generated direct impacts in expanding diaspora MSME networks, strengthening academic diplomacy, and enhancing the economic resilience of Indonesian migrant communities in Malaysia. This initiative reflects a concrete contribution to the internationalization of community service within the framework of the Tri Dharma of Higher Education.